Unveiling the Crucial Role of Chemical Enhancement in the SERS Analysis of Amphetamine-Metal Interactions on Gold and Silver Surfaces: Importance of Selective Amplification of the Narrow Interval of Vibrational Modes - Smeliková, Valerie; Kopal, Ivan; Člupek, Martin; Dendisová, Marcela; Švecová, Marie (Analytical chemistry, 2024)
The use of addictive substances, including drugs, poses significant health risks and contributes to various social problems, such as increased crime rates associated with substance-induced aggressive behavior. To address these challenges, possession of addictive substances is legally prohibited. However, detecting and analyzing these substances remain a complex task for law enforcement, primarily due to the presence of adulterants or limited sample quantities. In response to the evolving illicit market, continuous development and adaptation of analytical techniques are essential. One approach is the utilization of surface-enhanced Raman scattering (SERS) spectroscopy, which involves adsorbing the analyte onto nanostructured plasmonic surfaces. This study explores the potential of SERS in detecting amphetamine-based addictive stimulants with a specific focus on the properties of enhancing surfaces chosen. Comparative investigations were performed using silver and gold surfaces, with gold colloidal systems demonstrating a favorable performance. Moreover, to provide a comprehensive interpretation of the measured spectra, extensive density functional theory (DFT) calculations were conducted, allowing for a deeper understanding of the observed spectral features and molecular interactions with the metal surfaces. This review presents insights into the role of chemical enhancement in SERS analysis of amphetamine-metal interactions, shedding light on the selective amplification of vibrational modes. These findings, supported by DFT calculations, have implications in the fields of spectroscopy, physical chemistry, and drug analysis, providing valuable contributions to forensic applications and a deeper understanding of chemical enhancement phenomena. We present the impact of the secondary resonances of Stokes-scattered photons. This illustrates the significance of recognizing the constraints of the frequently employed "E4" approximation, even in measurements involving multiple molecules rather than single molecules.